2023
DOI: 10.2503/hortj.qh-015
|View full text |Cite
|
Sign up to set email alerts
|

Pepper (<i>Capsicum annuum</i>) Plants Harboring the Begomovirus Resistance Gene <i>pepy-1</i> Show Delayed Symptom Progress and High Productivity Under Natural Field Conditions

Abstract: Pepper yellow leaf curl disease (PepYLCD) caused by begomoviruses is one of the most devastating diseases affecting pepper (Capsicum spp.) production worldwide. In our previous study, a loss-of-function allele, pepy-1, encoding messenger RNA surveillance factor Pelota was identified as a begomovirus resistance gene from a C. annuum cultivar BaPep-5. In this study, to investigate the effectiveness of pepy-1 conferred resistance against begomovirus in the field, we conducted a three-year evaluation under natural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 56 publications
1
1
0
Order By: Relevance
“…Virus detection using the TBIA method showed that TMV and CMV were the most dominant viruses infecting chili plants in the field, either occurring as a single or mixed infection with other viruses (PepMoV and ChiVMV). These results complement to previous studies which reported various types of viruses associated with chili plants in Indonesia, such as Pepper yellow leaf curl Indonesia virus (PYLCIV) and Pepper yellow leaf curl Aceh virus (PYLCAV) (Hidayat, Haryadi, & Nurhayati, 2009;Kesumawati et al, 2019;Pohan et al, 2022), Polerovirus (Suastika, Hartono, Nyana, & Natsuaki, 2012), Potato virus Y (PVY) (Damiri, 2014), CMV and ChiVMV (Subekti, Hidayat, Nurhayati, & Sujiprihati, 2006), as well as TMV (Taufik, Khaeruni, & Rombe, 2011).…”
Section: Main Viruses Infecting Chili Plantssupporting
confidence: 89%
“…Virus detection using the TBIA method showed that TMV and CMV were the most dominant viruses infecting chili plants in the field, either occurring as a single or mixed infection with other viruses (PepMoV and ChiVMV). These results complement to previous studies which reported various types of viruses associated with chili plants in Indonesia, such as Pepper yellow leaf curl Indonesia virus (PYLCIV) and Pepper yellow leaf curl Aceh virus (PYLCAV) (Hidayat, Haryadi, & Nurhayati, 2009;Kesumawati et al, 2019;Pohan et al, 2022), Polerovirus (Suastika, Hartono, Nyana, & Natsuaki, 2012), Potato virus Y (PVY) (Damiri, 2014), CMV and ChiVMV (Subekti, Hidayat, Nurhayati, & Sujiprihati, 2006), as well as TMV (Taufik, Khaeruni, & Rombe, 2011).…”
Section: Main Viruses Infecting Chili Plantssupporting
confidence: 89%
“…[12] had been identified that C. annuum cultivar Perintis (BaPep-5) is a recessive resistance gene pepy-1 in peppers in controlled conditions of laboratory, this gene was effective against the bipartite begomoviruses PepYLCAV and PepYLCAV. Moreover, [13] showed that Perintis (BaPep-5) significantly higher fruit productivity compared to six other commonly cultivated pepper cultivars included Kencana (BaPep-4), and Perintis (BaPep-5) had the lowest PepYLCD incidence. State that the estimation of yield variables character character can be used as a consideration for efficient selection.…”
Section: The Effect Of Begomovirus Resistance On the Yield Of Some Ch...mentioning
confidence: 96%